PENGARUH PEMASARAN BERBASIS SYARIAH TERHADAP AFFILIATE DI MEDIA SOSIAL APLIKASI TIK TOK - Haway Mudaramsah (ISTISMAR, 2026)
Abstract: This research aims to determine and analyze the influence of Sharia-based marketing on affiliates in the Tik Tok social media application among students at the UNWAHA Jombang Islamic Faculty. The research method used is quantitative. Data collection was carried out by distributing questionnaires in the form of closed questions in the form of a Likert's Scale to 93 respondents. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 25. Consisting of validity tests, reliability tests and simple linear regression analysis. Based on the data results, it can be concluded that there is a significant positive influence of sharia-based marketing on affiliates on the Tik Tok social media application. These results can be proven by a simple linear regression test on the t test table with a value of 4.974 > t table test of 2.279 with a significant value of 0.000 < 0.05. So there is a positive influence of Sharia-Based Marketing on Affiliates on the Tik Tok Application Social Media (Ha) which is accepted, and there is no positive influence of Sharia-Based Marketing on Affiliates on the Tik Tok Application Social Media (Ho) rejected, or in other words Ho is rejected and Ha is accepted.